Weight Trajectories Among Youths Following Residential Relocation - Saucy, Apolline; Warkentin, Sarah; Milà, Carles; Coloma, Fabián; Yu, Zhebin; de Bont, Jeroen; Bergström, Anna; Boer, Jolanda M A; Dadvand, Payam; de Hoogh, Kees; Gehring, Ulrike; Klánová, Jana; et al. (JAMA network open, 2025)
IMPORTANCE: Overweight and obesity affect millions of children and adolescents worldwide, and its prevalence is increasing. OBJECTIVE: To investigate the associations of changes in the surrounding residential environment following relocation on childhood body mass index (BMI), focusing on 3 external exposome domains: air pollution, the built environment, and socioeconomic disadvantage. DESIGN, SETTING, AND PARTICIPANTS: This longitudinal cohort study used harmonized data from birth cohorts from the Netherlands (PIAMA), Sweden (BAMSE), and the Czech Republic (ELSPAC-CZ) participating in the EXPANSE (Exposome Powered Tools for Healthy Living in Urban Settings) project, with birth dates ranging between 1991 and 1997. Participants were youths aged 2 to 24 years who had experienced residential relocation during their follow-up. Analysis focused on within-individual changes resulting from relocation. k Means clustering characterized multiple exposures from the 3 external exposome domains. Fixed-effects linear models estimated associations of exposome changes with changes in age- and sex-standardized body mass index (z-BMI), adjusted for relevant covariates. This study was conducted between July 2023 and January 2025. EXPOSURES: Changes in 3 external exposome domains: (1) ambient air pollution from high-resolution surfaces; (2) the built environment, including green, blue, and gray spaces and light at night; and (3) area-level socioeconomic disadvantage indicators. Domain-specific exposome profiles were characterized as low-, medium-, and high-hazard environments. MAIN OUTCOME AND MEASURES: Changes in z-BMI. RESULTS: The study included 4359 participants (1467 from PIAMA, 1778 from BAMSE, and 1114 from ELSPAC-CZ). A total of 2215 (50.8%) were male. The mean (SD) age at inclusion was 3.0 (1.1) years, and mean (SD) age at moving was 7.7 (4.3) years. Parental education varied across cohorts. Mean (SD) z-BMI was 0.2 (1.1), 0.4 (1.0), and 0.1 (1.2) at baseline and 0.0 (1.0), 0.3 (1.0), and 0.1 (1.1) after moving in PIAMA, BAMSE, and ELSPAC-CZ, respectively. Moving to higher-hazard environments (more polluted, more gray space) was associated with increases in z-BMI for all domains in PIAMA; significant associations were also seen for some domains and exposures in BAMSE and ELSPAC-CZ. Specifically, an association between moving to a more built environment and increase in z-BMI was consistent across cohorts: an IQR increase in gray spaces was associated with increases of 0.04 (95% CI, 0.01-0.06) units and 0.05 (95% CI, 0.01-0.09) units in z-BMI in BAMSE and PIAMA, respectively. An IQR increase in air pollution hazard was associated with increases of 0.07 (95% CI, 0.02-0.12) units and 0.07 (95% CI, 0.01-0.14) units in z-BMI for nitrogen dioxide (NO2) and fine particulate matter (PM2.5), respectively, in PIAMA. Presence of effect modification by parental education and age at moving varied across cohorts. CONCLUSIONS AND RELEVANCE: In this multicountry cohort study of 4359 youths in the Netherlands, Sweden, and the Czech Republic, moving to greener, less urbanized environments was associated with healthy childhood BMI trajectories. Heterogeneity across cohorts highlighted the context-specific influence of external exposome domains on childhood weight.
Keywords: obezita dětí a dospívajících; Longitudinal Studies; Netherlands; Air Pollution; Socioeconomic Factors; mladý dospělý; Adolescent; vytvořené prostředí; dítě; Švédsko; Humans; Male; index tělesné hmotnosti; Residence Characteristics; socioekonomické faktory; Body Mass Index; hmotnostní křivka; předškolní dítě; znečištění ovzduší; Child; Body-Weight Trajectory; Built Environment; ženské pohlaví; Czech Republic; Environmental Exposure; mužské pohlaví; Česká republika; Nizozemsko; mladiství; lidé; Pediatric Obesity; charakteristiky bydlení; vystavení vlivu životního prostředí; Young Adult; longitudinální studie; Child, Preschool; Sweden; Female